Peran Komitmen Organisasi sebagai Pemoderasi Pengaruh Sistem Pengendalian Internal dan Kompetensi Sumber Daya Manusia terhadap Kualitas Laporan Keuangan Pemerintah Daerah - Atika Sari; Jacobus Widiatmoko (Ekonomis: Journal of Economics and Business, 2023)
The research intends to test and analyze the influence of internal control systems and human resource competence on the quality of local government financial statements moderated by organizational commitments. This research includes quantitative research with primary data obtained from the distribution of survey questionnaires. The population of this research was the State Civil Apparatus (ASN) in 25 Regional Apparatus of Temanggung Regency. The sample was determined by the purposive sampling method which then resulted in a total sample of 110 respondents. Hypotheses testing is carried out by the absolute value difference test method which is processed using the IBM SPSS 26 software program. The results concluded that the internal control system had a significant positive effect on the quality of local government financial statements. Meanwhile, the competence of human resources has an insignificant positive effect on the quality of local government financial statements. Then the results of this study also show that organizational commitment is not able to moderate the influence of the internal control system and the competence of human resources on the quality of local government financial statements.